The Problematics of Publishing in a Multicultural Context: The Politics of Letter H - Makwati, Luyanduhlobo; Tendaupenyu , Clive (Unisia, 2025)
This article looks at the correct usage of language in communication and the importance of language in communication and advertising with specific reference to notices pamphlets and other documents with specific reference to Ndebele materials. This study examines the historical roots of current linguistic challenges. It explores the factors that have allowed the continued use of incorrect language in respected institutions a practice that burdens both language users and consumers of related products. The article further looks at the economic comparative advantage which companies should ride upon since they are dealing with language as an economic variable. It is out of this realisation that the lack of will at all levels despite the previous studies that were done and recommendations having been made the language has remained stifled which has necessitated the research of this nature. The study finds no coordinated effort among authors, linguists, publishers, and commissioning editors, who often work in isolation, resulting in the proliferation of linguistically inaccurate materials.  Translators should be involved since translation is a highly specialized especially where target audiences differ. Be it English to any indigenous languages or vice versa the practice should seek the services of experts in the discipline of translation and publishing.